Kikuchi-Fujimoto disease: three case reports - Sousa, Alexandre de Andrade; Soares, João Marcos Arantes; Santos, Marco Homero de Sá; Martins, Marcelo Portes Rocha; Salles, José Maria Porcaro (São Paulo Medical Journal, 2010)
CONTEXT: Kikuchi-Fujimoto disease (KFD) manifests in most cases as unilateral cervical lymphadenomegaly, with or without accompanying fever. The disease mainly affects young women and has a self-limited course. It is more common in oriental countries, with few reports of its occurrence in Brazil. KFD should be included in the differential diagnosis of suspected cases of viral infections, tuberculosis, reactive lymphadenitis, systemic lupus erythematosus and metastatic diseases. It can be histologically confused with lymphoma. The disease is benign and self-limiting and an excisional biopsy of an affected lymph node is necessary for diagnosis. There is no specific therapy. CASE REPORTS: This study reports on three cases of non-Asian female patients with KFD who were attended at our service between 2003 and 2006. A review of the literature was carried out, with a systematic search on this topic, with the aim of informing physicians about this entity that is manifested by cervical masses and fever.